Interspecies variation in the susceptibility of adult Pacific salmon to toxic urban stormwater runoff. (July 2018) - McIntyre, Jenifer K.; Lundin, Jessica I.; Cameron, James R.; Chow, Michelle I.; Davis, Jay W.; Incardona, John P.; Scholz, Nathaniel L.
Abstract: Adult coho salmon ( Oncorhynchus kisutch ) prematurely die when they return from the ocean to spawn in urban watersheds throughout northwestern North America. The available evidence suggests the annual mortality events are caused by toxic stormwater runoff. The underlying pathophysiology of the urban spawner mortality syndrome is not known, and it is unclear whether closely related species of Pacific salmon are similarly at risk. The present study co-exposed adult coho and chum ( O. keta ) salmon to runoff from a high traffic volume urban arterial roadway. The spawners were monitored for the familiar symptoms of the mortality syndrome, including surface swimming, loss of orientation, and loss of equilibrium. Moreover, the hematology of both species was profiled by measuring arterial pH, blood gases, lactate, plasma electrolytes, hematocrit, and glucose. Adult coho developed behavioral symptoms within a few hours of exposure to stormwater. Various measured hematological parameters were significantly altered compared to coho controls, indicating a blood acidosis and ionoregulatory disturbance. By contrast, runoff-exposed chum spawners showed essentially no indications of the mortality syndrome, and measured blood hematological parameters were similar to unexposed chum controls. We conclude that contaminant(s) in urban runoff are the likely cause of the disruption of ion balance and pH in coho but not chum salmon. Among the thousands of chemicals in stormwater, future forensic analyses should focus on the gill or cardiovascular system of coho salmon. Because of their distinctive sensitivity to urban runoff, adult coho remain an important vertebrate indicator species for degraded water quality in freshwater habitats under pressure from human population growth and urbanization. Graphical abstract: Image 1 Highlights: Adult coho salmon suffer high rates of acute spawning mortality in urban watersheds. Exposing adult coho to urban road runoff re-creates symptoms and mortality within hours. Arterial blood from exposed coho shows changes in blood parameters vs control coho. Co-exposed chum salmon spawners do not become visibly sick, nor show changes in blood. Coho salmon are uniquely sensitive to contaminants in urban road runoff. Abstract : Coho but not chum salmon spawners are susceptible to osmorespiratory toxicity from urban stormwater runoff.